2016
DOI: 10.1016/j.jmatprotec.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental studies of surface-pulsed magneto-oscillation on solidification

Abstract: a b s t r a c tExperimental and numerical methods were used to study the distribution of magnetic field, flow field, temperature, and solidification structure in pure Al under surface-pulsed magneto-oscillation (SPMO). The numerical modeling showed that electromagnetic force changed with time and location in molten Al. In the melt, electromagnetic force resulted in cyclic tensile and compressive loads and in intensive forcedconvection. Application of SPMO refined the solidified structure and reoriented the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The results show that the velocity magnitude first increases to the maxima quickly then decreases slowly after multiple cycles and finally reaches a stable with showing the periodic oscillation. The obtained results are consistent with that reported by Zhao et al (2016) and Chen and Shen (2018). The reason of the rapid rise in velocity magnitude is that the high temperature melts located at the interior liquid pool and shunt plate have been transferred to the side surface of the melt due to the forced flow with applying the magnetic field.…”
Section: Resultssupporting
confidence: 91%
“…The results show that the velocity magnitude first increases to the maxima quickly then decreases slowly after multiple cycles and finally reaches a stable with showing the periodic oscillation. The obtained results are consistent with that reported by Zhao et al (2016) and Chen and Shen (2018). The reason of the rapid rise in velocity magnitude is that the high temperature melts located at the interior liquid pool and shunt plate have been transferred to the side surface of the melt due to the forced flow with applying the magnetic field.…”
Section: Resultssupporting
confidence: 91%
“…They found that the distribution of the flow field is stable after 16 pulse cycles. Zhao et al [12] studied the distributions of the magnetic field, flow field, and temperature field in pure aluminum under surface-pulsed magneto-oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…The above simulations only considered the melts themselves [7][8][9][10][11][12][13]. The material parameters such as resistivity used to calculate the magnetic field and electromagnetic force in the above calculation mode were those of the pure melt.…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulation results showed that Joule heat varied with time and space and the maximum of value of Joule heat appeared at T/2 [19]. Distribution analyses of Joule heat at T/2 in SPMO, HPMO and CPMO with the same pulsed current parameters showed that Joule heat was concentrated near the coil (Fig.…”
Section: Distribution Of Joule Heatmentioning
confidence: 78%